Answer:
D
Step-by-step explanation:
i took the test trust me
Answer:
0
Step-by-step explanation:
The question lacks the graph to be able to solve it, I was doing a little research and I could find the graph which I will attach:
Already with the figure we can solve the question.
We have that the average exchange rate in this case would only take the normal slope between those 2 lines
. Furthermore we know that the slope (m) is given by:
m = (y2-y1) / (x2 - x1)
From the graph we have to:
y2 = 0
y1 = 0
x2 = 5
x1 = 3
we replace:
m = (0-0) / (5 - 3)
m = 0
Therefore the average rate is 0.
It’s A because (-2)2+(4)2-2(-2)+4(4)+8=0
-4+8+4+-16+8
(8+8) (-4+4) (-16)
16 -16 =0
Y = 9x means each box of the new brand is $9.
<span>So the old brand is $2 per box more. I know you </span>
<span>can do part B now!
Hope that helps!!!!!!!!!</span>
Answer:
7
Step-by-step explanation:
(x+3)/(x+8) = 2/3
3x + 9 = 2x + 16
x = 7